2016
DOI: 10.1515/intox-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Original Article. Toxicity of Glandularia selloi (Spreng.) Tronc. leave extract by MTT and neutral red assays: influence of the test medium procedure

Abstract: Cytotoxicity assays using cell cultures may be an alternative to assess biological toxicity of plant extracts with potential phytotherapeutic properties. This study compared three methods to prepare culture media for the exposure of Vero cells to plant extracts. Leaves of Glandularia selloi (Spreng.) Tronc. were used to prepare culture medium with aqueous extract, extract in culture medium and methanol extract. Toxicity was assessed using the MTT and neutral red (NR) assays. In general, alterations in the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The cytotoxicity effect of OPL extracts, flavonoid enriched fractions and flavonoid C-glycosides was determined by MTT assay in 3T3 cells treated with different gradient concentrations (1.56, 3.13, 6.25, 12.5 and 25, μg/mL). Figure 4 shows that all concentrations of OPL extracts, flavonoid enriched fractions and flavonoid C-glycosides have no toxicity effect on 3T3 cells indicated by the cell viability percentage reached above 70% [21]. The results showed that the concentration of samples at 1.563-25 μg/mL showed 79-155% cell viability after 48 h incubation.…”
Section: Effect Of Opl Extracts Flavonoid Enriched Fractions and Flamentioning
confidence: 95%
“…The cytotoxicity effect of OPL extracts, flavonoid enriched fractions and flavonoid C-glycosides was determined by MTT assay in 3T3 cells treated with different gradient concentrations (1.56, 3.13, 6.25, 12.5 and 25, μg/mL). Figure 4 shows that all concentrations of OPL extracts, flavonoid enriched fractions and flavonoid C-glycosides have no toxicity effect on 3T3 cells indicated by the cell viability percentage reached above 70% [21]. The results showed that the concentration of samples at 1.563-25 μg/mL showed 79-155% cell viability after 48 h incubation.…”
Section: Effect Of Opl Extracts Flavonoid Enriched Fractions and Flamentioning
confidence: 95%
“…Moreover, tested compounds may influence (enhance or reduce) succinate dehydrogenase activity without affecting the survival of the cells or may even directly interact with the MTT. The possibility of chemical reactions with MTT is particularly important when assessing the cytotoxicity of plant extracts since they are complex mixtures of compounds with versatile properties, including reductive activity, such as antioxidants [ 70 ]. Since there is no universal approach to cytotoxicity testing, using at least two assays based on the assessment of different parameters may be considered a good practice.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, when chloroquine was tested, the NR indicated 100-fold higher toxicity than MTT because enzymatic assays like MTT may be influenced by enzyme inhibitors such as chloroquine [46]. Both NR and MTT assays use measurements of absorbance to calculate the number of viable cells after exposure to various xenobiotics, and both assays have their advantages but also significant disadvantages [70,71]. The NR assay indicates toxicity of substances Studies showed that the NR and the MTT assay are among the most sensitive cytotoxicity assays showing statistically significant differences between the treated cells and the untreated controls.…”
Section: Cytotoxic Activity (Ccmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were exposed to different concentrations of extracts ranging from 1000 to 3.91 µg mL −1 . As depicted in Figure S3, the extracts showed no toxicity effect on 3T3 cells within tested concentrations indicated by the cell viability percentage reached above 70% except for GLY and BD extracts at 1000 µg mL −1 [46]. However, a dose-dependent effect within tested samples whereby the cell viability increased as the extract concentration decreased was observed.…”
Section: Cell Viablity Of Opl-nades Extractsmentioning
confidence: 86%